Performance of seven different paediatric early warning scores to predict critical care admission in febrile children presenting to the emergency department: a retrospective cohort study. Issue 5 (4th May 2021) - Romaine, Sam T; Sefton, Gerri; Lim, Emma; Nijman, Ruud G; Bernatoniene, Jolanta; Clark, Simon; Schlapbach, Luregn J; Pallmann, Philip; Carrol, Enitan D
Abstract : Objective: Paediatric Early Warning Scores (PEWS) are widely used in the UK, but the heterogeneity across tools and the limited data on their predictive performance represent obstacles to improving best practice. The standardisation of practice through the proposed National PEWS will rely on robust validation. Therefore, we compared the performance of the National PEWS with six other PEWS currently used in NHS hospitals, for their ability to predict critical care (CC) admission in febrile children attending the emergency department (ED). Design: Retrospective single-centre cohort study. Setting: Tertiary hospital paediatric ED. Participants: A total of 11 449 eligible febrile ED attendances were identified from the electronic patient record over a 2-year period. Seven PEWS scores were calculated (Alder Hey, Bedside, Bristol, National, Newcastle and Scotland PEWS, and the Paediatric Observation Priority Score, using the worst observations recorded during their ED stay. Outcomes: The primary outcome was CC admission within 48 hours, the secondary outcomes were hospital length of stay (LOS) >48 hours and sepsis-related mortality. Results: Of 11 449 febrile children, 134 (1.2%) were admitted to CC within 48 hours of ED presentation, 606 (5.3%) had a hospital LOS >48 hours. 10 (0.09%) children died, 5 (0.04%) were sepsis-related. All seven PEWS demonstrated excellent discrimination for CC admission (range area under the receiver operating characteristic curves (AUC) 0.91–0.95) and sepsis-related mortality (range AUC 0.95–0.99), most demonstrated moderate discrimination for hospital LOS (range AUC 0.69–0.75). In CC admission threshold analyses, bedside PEWS (AUC 0.90; 95% CI 0.86 to 0.93) and National PEWS (AUC 0.90; 0.87–0.93) were the most discriminative, both at a threshold of ≥6. Conclusions: Our results support the use of the proposed National PEWS in the paediatric ED for the recognition of suspected sepsis to improve outcomes, but further validation is required in other settings and presentations.